(untitled) (Legislatif, 2026)
Abstract The research in this article aims to analyze the integration of Islamic law and customary law in the practice of adat badamai among contemporary Banjar society as an effort to deconstruct the colonial Receptie Theory. Using a normative-empirical legal research method with a legal history approach, this study examines how Islamic values such as ishlah and diyat organically merge within the structure of local tradition. The findings reveal that the separation between adat and religion in Banjar Land represents a colonial epistemological failure, as for the Banjar people, Islam is the substance (soul) while adat is the vessel (body). The main findings reveal that the bapapatutan mechanism within adat badamai proves effective as a restorative justice instrument that transcends the logic of formal law. Through bapapatutan, the determination of compensation is flexible, based on the principles of propriety and willingness, in order to restore social harmony and pursue barakat (blessings). Juridically, this practice represents the living law, which gains strong legitimacy through Articles 2 and 597 of Law No. 1 of 2023 (the New Criminal Code). This recognition provides binding force for the fulfillment of customary obligations within the national criminal justice system. This study concludes that strengthening the synergy between customary institutions and law enforcement authorities is crucial for maintaining sociological order based on local wisdom. This transformation directs the national legal system toward a more humane direction by adopting dispute resolution mechanisms that are not merely retributive, but also heal social wounds through divine and humanitarian values.